2009
DOI: 10.1057/jmm.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

The effect of marketing strategy and marketing capability on business performance. Case study: Iran's medical equipment sector

Abstract: In this article, the relationship between marketing strategy and the marketing capability of three categories of business performance – overall, financial and non-financial – has been investigated using a questionnaire including 30 parameters. The acceptable Cronbach's α in the questionnaire is considered to be 0.80. The multiple regression tests indicate that marketing strategy has no effect on the overall performance (β= 0.001; t = 0.005), whereas it shows a positive effect on non-financial performance (β = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
2
14
0
3
Order By: Relevance
“…According to above market orientation elements, Azizi et al (2009) developed a questionnaire to measure the market orientation of enterprises. The questionnaire allowed researchers actually measuring the behavior of an enterprise taking market orientation, rather than halting market orientation for a belief and slogan.…”
Section: Market Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to above market orientation elements, Azizi et al (2009) developed a questionnaire to measure the market orientation of enterprises. The questionnaire allowed researchers actually measuring the behavior of an enterprise taking market orientation, rather than halting market orientation for a belief and slogan.…”
Section: Market Orientationmentioning
confidence: 99%
“…The definition in this study is therefore referred to Abebe and Angriawan (2014) in order not to confuse with the complete market orientation idea. Azizi et al (2009) indicated that both market oriented culture and market information processing had to be covered in order to completely measure market orientation (Kim and AtuaheneGima 2010). In regard to cultural market orientation, the dimensions proposed by Abebe and Angriawan (2014) are utilized in this study, and long-term view and profitability are deleted, because most researchers merely applied customer orientation, competitor orientation, and interfunctional coordination to the research (Meyer 2011).…”
Section: Market Orientationmentioning
confidence: 99%
“…In other words, CRM antecedes the development of marketing capabilities in the organization, because marketing capability is an incorporated process that is designed to utilize the skills and resources, and corporate knowledge, and it enables businesses to better satisfy the needs of the customers through adding value services to their products (Azizi et al, 2009). …”
Section: Crm Technology Marketing Capabilities and Organizational Pmentioning
confidence: 99%
“…In the era of global competition, this becomes a big challenge for management team. It goes without saying that companies need to investigate and apply a differentiated strategy versus others to stand out in the crowd (Azizi et al, 2009). Only company that has competitive advantage will be able to perform as expected.…”
Section: Introductionmentioning
confidence: 99%